2001
DOI: 10.1021/je010193l
|View full text |Cite
|
Sign up to set email alerts
|

Solubility of 1,1,1,2-Tetrafluoroethane in Triethylene Glycol Dimethyl Ether

Abstract: The solubility of 1,1,1,2-tetrafluoroethane in triethylene glycol dimethyl ether was measured by the static method in the temperature range (283.15 to 353.15) K. Triethylene glycol dimethyl ether was completely miscible with 1,1,1,2-tetrafluorethane in the range of temperatures and pressures studied. All experimental solubility data were correlated by the five-parameter NRTL equation with a very small overall average absolute deviation. This binary system exhibited large negative deviations from Raoult's law.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 12 publications
2
32
1
Order By: Relevance
“…Also these experimental points are represented with an acceptable accuracy by the model, even if the deviations are higher than those for the data given in the present work. From the results obtained, it can be concluded that there is good agreement between the new measurements and the literature data from reference [3]. The activity coefficient values, obtained from the present experimental data and calculated from the Wilson model, are shown in figure 4.…”
Section: Data Correlationsupporting
confidence: 80%
See 3 more Smart Citations
“…Also these experimental points are represented with an acceptable accuracy by the model, even if the deviations are higher than those for the data given in the present work. From the results obtained, it can be concluded that there is good agreement between the new measurements and the literature data from reference [3]. The activity coefficient values, obtained from the present experimental data and calculated from the Wilson model, are shown in figure 4.…”
Section: Data Correlationsupporting
confidence: 80%
“…Coronas et al [3], in their work for the same mixture at similar temperatures and over similar composition ranges, stated that all the activity coefficients for R134a under their experimental conditions are less than 1. This is an evident disagreement with the behaviour found here.…”
Section: Data Correlationmentioning
confidence: 95%
See 2 more Smart Citations
“…However, in spite of their importance, there are only a few studies available in the literature on the thermophysical properties of the HFC-134a + PGDME system [2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%